Fenomena krisis moral dalam era digital dan perspektif tentang akhlak islam - Andriani, Nadia Rizki (Maliki Interdisciplinary Journal, 2025)
The digital era has brought about major transformations in social interactions, information access, and lifestyles. However, this technological advancement has also given rise to a moral crisis, such as the emergence of hoax news, hate speech, a culture of showing off, pornography, and a loss of empathy. This problem is rooted in weak self-control in the use of digital freedom. This research uses a literature review approach to analyze the moral crisis in the digital era and examine it through the perspective of Islamic morality. Islam offers comprehensive solutions in the form of tazkiyah an-nafs (purification of the soul), amar ma'ruf nahi munkar (encouraging good and preventing evil), muraqabah (awareness of God's supervision), and the application of Islamic digital ethics. The results of the study indicate that the application of Islamic moral principles can serve as a moral bulwark in facing the challenges of the digital world. In conclusion, overcoming the digital moral crisis requires a holistic approach involving individual empowerment through morality, the role of the family, Islamic digital literacy education, and fair and firm government regulations. Thus, Islamic morality not only functions to maintain individual morality but also to build a dignified and civilized digital society.